Optics Express: "Metre-per-second microfluidic flow velocimetry with dual beam optical coherence tomography" Rigas Hallam Charrett Ford Tatam - Hallam, Jonathan M.; Tatam, Ralph P.; Charrett, Tom; Rigas, Evangelos; Ford, Helen (Cranfield University, 2019)
Images and analysis code associated with Optics Express publication: "Metre-per-second microfluidic flow velocimetry with dual beam optical coherence tomography". The code should be run in a jupyter notebook (or other python implementation).
Keywords: OCT'; 'PIV'; 'Particle Image Velocimetry'; 'Particle Tracking Velocimetry'; 'PTV'; 'Optical Coherence Tomography'; 'Interferometry'; 'Flow Velocimetry'; 'Microfluidics'; 'Microtechnology'; 'Photonics and Electro-Optical Engineering (excl. Communications)'; 'Optical Technology'; 'Photodetectors; Optical Sensors and Solar Cells'; 'Nonlinear Optics and Spectroscopy'; 'Flow Analysis'